Benefits of Soft Skills for Managers of Deal Operation Centre (DOC), Hitachi Vantara (HV) in Kuala Lumpur - Dev, Kumar Philip Sanker (2023)
Soft skills have become a subject of increasing interest in managers’ development. Soft skills development is aimed to enable and enhance professional development, participation in learning, and engagement as well as success in career development. This study aims to assess and understand the benefits of soft skills for managers of Deal Operations Centre (DOC), Hitachi Vantara (HV) in Kuala Lumpur, Malaysia. There were four areas of interest examined in this study: awareness of soft skills, the benefit of soft skills, types of soft skills, and disadvantages of inadequate soft skills. The research was targeted into two groups: one (1) director and ten (10) managers. The population of the study consisted of 55% from the age group 45 and above and as for the gender, 73% of the respondents were male. All eleven (11) respondents acquired a minimum bachelor’s degree and above as this was the entry qualification for a manager position. As for the length of service, 55% of the respondents have worked in their current position for at least ten (10) years. The approach used for this study was a qualitative methodology combining one (1) key informant interview and ten (10) semi-structured interviews. The result of the study highlights the significance of soft skills for managers in achieving continuous success for themselves and their teams. The five key soft skills identified - communication, leadership, teamwork, relationship building, and positive attitude - play a crucial role in effective management. The study's implications are significant. Managers who prioritize the development of soft skills can expect various benefits. Effective communication and teamwork lead to greater productivity through efficient collaboration within the team. Positive relationships built through relationship building skills result in improved employee engagement. Strong leadership and organizational skills enable managers to manage workload effectively. Furthermore, possessing these soft skills makes managers more likely to deliver positive outcomes by motivating and inspiring their teams. The study also suggests that well-developed soft skills contribute to better self-confidence, enhancing overall leadership qualities and driving performance excellence. The findings of this study show that soft skills are imperative among managers to lead themselves and their teams in the direction of unceasing success. The five key soft skills identified through the study were communication, leadership, teamwork, relationship building, and positive attitude. This study also indicates that the benefits of soft skills are manifold. These benefits include greater productivity, improved employee engagement, better ability to manage workload, greater ability to deliver positive outcomes, better self-confidence, and leadership qualities that can drive performance excellence. Four recommendations were deduced from this study. The first suggestion is that managers should include soft skills in their learning, retraining, and upskilling. Additionally, it was recommended that soft skills are included in their performance management system's competencies, doing so will highlight how crucial they are in the workplace. Next, it was recommended that the managers need to align themselves with digital and technological advancement to keep themselves abreast with the ever-shifting skill sets. The final recommendation would be managers need to ensure they equip themselves with a new set of soft skills such as adaptability, embracing change, and working collaboration during this unprecedented turn of events such as the pandemic and other calamities.